Debt Moratoria: Evidence from Student Loan Forbearance - Michael Dinerstein; Constantine Yannelis; Ching-Tse Chen (Center for Economic Studies and ifo Institute (CESifo), 2023)
We evaluate the effects of the 2020 student debt moratorium that paused payments for student loan borrowers. Using administrative credit panel data, we show that the payment pause led to a sharp drop in student loan payments and delinquencies for borrowers subject to the debt moratorium, as well as an increase in credit scores. We find a large stimulus effect, as borrowers substitute increased private debt for paused public debt. Comparing borrowers whose loans were frozen with borrowers whose loans were not frozen due to differences in whether the government owned the loans, we show that borrowers used the new liquidity to increase borrowing on credit cards, mortgages, and auto loans rather than avoid delinquencies. The effects are concentrated among borrowers without prior delinquencies, who saw no change in credit scores, and we see little effects following student loan forgiveness announcements. The results highlight an important complementarity between liquidity and credit, as liquidity increases the demand for credit even as the supply of credit is fixed.
Keywords: G51; I22; 330; debt moratoria; student loans